Analisis Total Productive Maintenance (TPM) Dengan Menggunakan Metode Overall Equipment Effectiveness Pada Mesin Drayer Di PT. IJK - Kharis Gunawan; Osep Hijuzaman; Akbar, Ali (Jurnal Teknologika, 2024)
PT.IJK. has implemented Total Productive Maintenance to improve the efficiency and effectiveness of the manufacturing company as a whole. However, the implementation is still not optimal as seen from the high incidence of machine damage and the value of machine downtime. This study aims to measure the value of equipment effectiveness, find the root cause of the problem and provide suggestions for improvement. The research was conducted on the drayer machine which has the highest breakdown rate. The study began by measuring the achievement of overall equipment effectiveness (OEE) value, then identifying the six big losses that occur. The results showed that the average OEE value on the drayer machine was 76.36%, this effectiveness value is classified as very low because the standard OEE value for world-class companies is ideally 85%. The biggest factor affecting the low OEE value is the performance rate with a percentage factor of six big losses on Reduced speed loss of 18.17% of the entire time loss. The proposed corrective action is to prepare autonomous maintenance equipment, provide training for operators and maintenance technicians and supervise operators regarding workplace cleanliness.